Planning world cites : - Newman, Peter (Palgrave Macmillan, 2005)
This internationally comparative text on urban planning covers both the global and regional context in which it takes place and the different combinations of issues confronting different types of cities. In contrast to existing texts the book considers both what have traditionally been regarded as "world cities" (London, New York, Tokyo) and a range of other important cities in the European, American and Asian regions. The core of the book focuses on an assessment of the strategic policy and planning options for major cities in response to globalization and other key issues and challenges of the twenty-first century.